Lemierre’s syndrome: a forgotten disease - Pilarz, Anna; Sosin, Julia; Salamon, Dariusz; Stachowiak, Julia; Zwierzchowska, Maria; Sojka, Aleksandra; Domagała, Wojciech (Quality in Sport, 2024)
Lemierre’s syndrome or Lemierre’s disease is septicemia in the course of angina. It is a rare disease that occurs during or after pharyngitis and appears as inflammation of the internal jugular vein and subsequent embolic abscesses in the lungs or viscera. It is most commonly seen in teenagers and young adults. Lemierre’s syndrome has long been treated as a forgotten disease, but its incidence is now rising again. Aim of the study: Due to the high prevalence of benign oral and pharyngeal infections in adolescents, the diagnosis of Lemierre’s syndrome is often difficult to catch initially. This can result in delays in treatment. This work describes the diverse presentation of Lemierre’s syndrome, diagnostic options, and highlights the role of the interdisciplinary team in the care of these patients. Materials and methods: A systematic review of scientific and medical literature from the PubMed and Google Scholar databases was conducted. Results: Given the potential catastrophic consequences, including septicemia, multiple organ failure and death, it is imperative to quickly recognize Lemierre’s syndrome based on the clinical picture, followed by targeted diagnostic testing and immediate initiation of broad-spectrum antibiotics. Increasing awareness of Lemierre’s syndrome among physicians is key to facilitating rapid diagnosis and life-saving treatment.